(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Sizonenko I. G. Analysis of results of verification of efficiency of process of legal socialization of children-orphans teens in general school, boarding school. In the article the analysis of process of teen-orphans’ legal socialization in boarding-school of general education is presented.